PERLINDUNGAN DAN PEMENUHAN HAK ANAK DALAM PERSPEKTIF HAK ASASI MANUSIA - Ratihpuspita Krisnowo (Law Department, University of Widya Gama Mahakam Samarinda, 2026)
The protection of children's rights is an essential component of the human rights system aimed at ensuring the fulfillment of children's fundamental rights. However, violations of children's rights continue to occur in various forms, indicating the need for stronger legal protection and policy implementation. This study aims to analyze the concept of child protection from a human rights perspective, examine the implementation of child protection within the Indonesian legal system, and identify the challenges and efforts to strengthen the protection of children's rights. The research questions address the concept of child protection in the human rights framework, its implementation in Indonesia, and the existing challenges in strengthening child protection.This research applies a normative legal method using statutory and conceptual approaches. The data consist of primary, secondary, and tertiary legal materials obtained through literature study. The results indicate that child protection within the human rights perspective recognizes children as legal subjects who possess the rights to survival, development, and protection from violence and discrimination. In Indonesia, the protection of children's rights has been regulated through several legal instruments, particularly Law Number 35 of 2014 concerning Child Protection. Nevertheless, its implementation still faces several challenges, including weak law enforcement and limited public awareness. Therefore, strengthening the child protection system requires improved law enforcement, stronger institutional support, and active community participation.